A POSSIBLE CALEDONIDE ARM THROUGH THE BARENTS SEA IMAGED BY OBS DATA - Breivik A.J.; Mjelde R.; Grogan P.; Shimamura H.; Murai Y.; Nishimura Y.; Kuwano A. (My University, 2002)
The assembly of the crystalline basement of the western Barents Sea is related to the Caledonian orogeny during the Silurian. However, the development southeast of Svalbard is not well understood, as conventional seismic reflection data does not provide reliable mapping below the Permian sequence. A wide-angle seismic survey from 1998, conducted with ocean bottom seismometers in the northwestern Barents Sea, provides data that enables the identification and mapping of the depths to crystalline basement and Moho by ray tracing and inversion. The four profiles modeled show pre-Permian basins and highs with a configuration distinct from later Mesozoic structural elements. Several strong reflections from within the crystalline crust indicate an inhomogeneous basement terrain. Refractions from the top of the basement together with reflections from the Moho constrain the basement velocity to increase from 6.3 km s−1 at the top to 6.6 km s−1 at the base of the crust. On two profiles, the Moho deepens locally into root structures, which are associated with high top mantle velocities of 8.5 km s−1. Combined P- and S-wave data indicate a mixed sand/clay/carbonate lithology for the sedimentary section, and a predominantly felsic to intermediate crystalline crust. In general, the top basement and Moho surfaces exhibit poor correlation with the observed gravity field, and the gravity models required high-density bodies in the basement and upper mantle to account for the positive gravity anomalies in the area. Comparisons with the Ural suture zone suggest that the Barents Sea data may be interpreted in terms of a proto-Caledonian subduction zone dipping to the southeast, with a crustal root representing remnant of the continental collision, and high mantle velocities and densities representing eclogitized oceanic crust. High-density bodies within the crystalline crust may be accreted island arc or oceanic terrain. The mapped trend of the suture resembles a previously published model of the Caledonian orogeny. This model postulates a separate branch extending into central parts of the Barents Sea coupled with the northerly trending Svalbard Caledonides, and a microcontinent consisting of Svalbard and northern parts of the Barents Sea independent of Laurentia and Baltica at the time. Later, compressional faulting within the suture zone apparently formed the Sentralbanken High.